Raman Spectroscopy of Fullerenes: From C60 to Functionalized Derivatives - Yifan Qin; Jilian Xu; Zhewen Liang; Haijun Teng; Da Zhan; Hai Xu (Molecules)
Fullerenes, a unique allotrope of carbon, have captured significant attention in multiple scientific fields. As a non-destructive characterization technique, Raman spectroscopy has proven indispensable for investigating fullerenes and their derivatives, offering detailed insights into their vibrational properties. This review discusses the broad utility of Raman spectroscopy in revealing the structural and physicochemical characteristics of fullerenes—from the iconic C60 molecule to an array of its derivatives—highlighting its capacity to detect functionalization-induced changes in molecular structure and electronic properties, while also assessing environmental influences such as solvent effects and temperature variations. Particular emphasis is placed on advanced Raman-based techniques, including enhanced Raman spectroscopy, surface-enhanced Raman spectroscopy (SERS), and tip-enhanced Raman spectroscopy (TERS), for the characterization of fullerenes and their derivatives. These cutting-edge methods offer high sensitivity and ultra-high spatial resolution, greatly expanding the scope of fullerene research and delivering deeper insights into their structural and functional properties.